Production process of biodegradable environment-friendly plastic

By optimizing raw material ratio and process parameters, combining high-efficiency surface modification and bio-based protective film, the problem of difficult to take into account both material stability and degradation performance in the prior art is solved, and high stability and rapidity of biodegradable environmentally friendly plastics are achieved Degradation effect.

CN119161619APending Publication Date: 2024-12-20SHENZHEN YIMING PACKAGING TECH CO LTD

Patent Information

Application Number
CN202411480455.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing biodegradable environmentally friendly plastic production processes are difficult to take into account the stability of the material during its service life and the rapid and complete biodegradable properties after being discarded, especially after surface modification treatment and protective film coating, which may be affected.

Method used

By optimizing the raw material ratio of polylactic acid and corn starch, improving the bio-based plasticizer addition method, strictly controlling the temperature and pressure parameters of extrusion granulation and injection molding, and introducing efficient surface modification technology and bio-based protective film coating The coating process ensures that the material is stable during its service life and degrades rapidly after being discarded.

Benefits of technology

The balance between mechanical properties and biodegradability of polylactic acid and corn starch materials is achieved, and the stability and degradation performance of the materials are improved, ensuring that the product is durable during its service life and quickly degrades after being discarded, reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161619A_ABST
    Figure CN119161619A_ABST
Patent Text Reader

Abstract

The invention discloses a biodegradable environment-friendly plastic production process which comprises the following steps: a) raw material selection: selecting a mixture of polylactic acid and corn starch in a specific proportion; b) uniformly mixing the polylactic acid and the corn starch in the step a) according to a weight ratio; c) adding a specific proportion of a bio-based plasticizer into the mixture in the step b); d) carrying out extrusion granulation treatment on the mixture in the step c); e) performing injection molding on the particles obtained in the step d) to prepare the particles into required shapes; f) controlling temperature and pressure parameters in the forming process of e); (g) carrying out surface modification treatment on the product prepared in the step (f) to enhance the weather resistance of the product; h) coating the surface of the product treated in the step g) with a layer of bio-based protective film; and i) carrying out an aging test on the coated product in the step h) to verify the stability of the coated product in the use period and the degradation performance of the coated product after being discarded. The biodegradable environment-friendly plastic prepared by the method disclosed by the invention can be quickly degraded after being discarded while the stability and durability in the use period are ensured, so that the environmental pollution is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of waste treatment, and in particular relates to a production process of biodegradable and environmentally friendly plastics. Background Art

[0002] With the improvement of environmental protection awareness, traditional petroleum-based plastics are subject to more and more restrictions due to their difficulty in degradation. At present, a kind of biodegradable environmentally friendly plastic has appeared on the market, which is mainly made of natural ingredients such as polylactic acid (PLA) and corn starch. This material not only reduces the impact on the environment during the production process, but also can be degraded faster in the natural environment after being discarded, reducing environmental pollution.

[0003] The existing production process of biodegradable and environmentally friendly plastics generally includes the following steps: first, polylactic acid and corn starch are selected as the main raw materials and mixed in a certain proportion; then, an appropriate amount of bio-based plasticizer is added to the mixture to improve the flexibility and processing performance of the material; then, the mixed material is made into granules through an extrusion granulation process; then, the granules are processed into the desired finished products using injection molding technology; finally, the molded product is surface modified and coated with a layer of bio-based protective film to improve its weather resistance.

[0004] Although the existing production process has achieved certain results, there is still an important technical problem: how to ensure that the material has sufficient stability during its service life and can quickly and completely biodegrade after being discarded. Traditional practices often find it difficult to take both requirements into account, especially after surface modification and protective film coating, the degradation performance of the product may be affected. Summary of the invention

[0005] The purpose of the present invention is to provide a biodegradable and environmentally friendly plastic production process, which solves the problems raised in the above background technology by optimizing the raw material ratio, improving the plasticizer addition method, strictly controlling the temperature and pressure parameters of extrusion granulation and injection molding, and introducing efficient surface modification technology and bio-based protective film coating technology.

[0006] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a process for producing biodegradable and environmentally friendly plastics, comprising: a) selecting raw materials, selecting a mixture of polylactic acid and corn starch in a specific ratio; b) uniformly mixing the polylactic acid and corn starch in a) according to a weight ratio; c) adding a specific ratio of a bio-based plasticizer to the mixture in b); d) extruding and granulating the mixture in c); e) injection molding the particles obtained in d) into a desired shape; f) controlling temperature and pressure parameters during the molding process in e); g) performing surface modification treatment on the product prepared in f) to enhance its weather resistance; h) coating a layer of bio-based protective film on the surface of the product treated in g); i) performing an aging test on the coated product in h) to verify its stability during service life and its degradation performance after disposal.

[0007] Preferably, in step a), the specific ratio is a mass ratio of polylactic acid to corn starch of X:Y, wherein X ranges from 60 to 80, Y ranges from 20 to 40, and satisfies the formula X+Y=100;

[0008] Before mixing the raw materials, the polylactic acid is preheated to a temperature T1 of 50°C to 70°C; the preheated polylactic acid is mixed with corn starch in a mass ratio of X:Y; the mixture is kneaded through a twin-screw extruder, and the processing temperature of the extruder is set to T2 of 170°C to 190°C; during the kneading process, the screw speed S is controlled to remain at 30 to 50rpm.

[0009] Preferably, in step b), the weight ratio is the mass ratio of polylactic acid to corn starch Z:W, wherein Z ranges from 60 to 80, W ranges from 20 to 40, and satisfies the formula Z+W=100;

[0010] Using a high-speed mixer, polylactic acid and corn starch are mixed at a rotation speed R1 of 1000 to 1500 rpm. During the mixing process, the duration is T3, and T3 is 5 to 10 minutes;

[0011] After the mixing is completed, the mixture is cooled to room temperature T4, T4 not exceeding 25°C; the cooled mixture is graded through a sieve with an aperture D of 0.5 to 1.0 mm to remove large particles that are not mixed uniformly.

[0012] Preferably, in step c), the specific ratio is a weight ratio of the bio-based plasticizer to the mixture A:B, wherein A ranges from 5 to 15, B ranges from 85 to 95, and satisfies the formula A+B=100;

[0013] Adding a bio-based plasticizer in a weight ratio of A:B to the mixture, wherein A is in the range of 5 to 15, and then heating the mixture at a temperature T5, wherein T5 is in the range of 60°C to 80°C;

[0014] During the heating process, the stirring time T6 is continued, T6 is 10 to 20 minutes, until the plasticizer is completely integrated into the mixture; after completion, the obtained mixture is cooled to room temperature T7, T7 does not exceed 25°C.

[0015] Preferably, in step d), during the extrusion granulation process, the extruder screw speed V ranges from 20 to 40 rpm, the extrusion temperature T8 ranges from 170° C. to 190° C., and satisfies the formula T8-T9≥20° C., wherein T9 is the cooling section temperature;

[0016] The mixture in d) is fed into an extruder, and the screw speed V is set to 20 to 40 rpm; during the extrusion process, the extrusion temperature T8 is controlled to be maintained at 170° C. to 190° C.; under the extrusion temperature condition, it is ensured that the cooling section temperature T9 is at least 20° C. lower than T8; after completion, the extruded strip material is pelletized to obtain particles with a particle size D1 of 2 to 5 mm.

[0017] Preferably, in step e), during injection molding, the mold temperature T10 ranges from 40°C to 60°C, the injection pressure P1 ranges from 60 to 80 MPa, and satisfies the formula P1×T10≤4500;

[0018] Put the pellets into the injection molding machine, set the mold temperature T10 to 40℃ to 60℃, and set the injection pressure P1 to 60 to 80MPa; under the injection pressure condition, control the holding time T11 to 10 to 30 seconds; after completion, cool the product to room temperature T12, T12 not exceeding 25℃, to complete the molding.

[0019] Preferably, in step f), in controlling the temperature and pressure parameters, the mold temperature T13 ranges from 40°C to 60°C, the injection pressure P2 ranges from 60 to 80 MPa, and satisfies the formula T13×P2≤4800;

[0020] During the molding process, the mold temperature T13 is set to 40°C to 60°C, and the injection pressure P2 is set to 60 to 80 MPa;

[0021] Under the injection pressure condition, control the holding time T14 to 10 to 30 seconds; during the holding time, ensure that the cooling water flow F1 is 1 to 2 liters / minute; under the cooling water flow condition, wait for the product to cool to room temperature T15, T15 does not exceed 25°C to complete the molding.

[0022] Preferably, in g), in the surface modification treatment, the coating thickness L ranges from 0.1 to 0.3 mm, the coating liquid concentration C ranges from 5 to 10%, and satisfies the formula C×L≤3;

[0023] Preparing a coating liquid with a concentration C of 5 to 10% for surface treatment of the product in g);

[0024] Immerse the product prepared in the above into the coating liquid for a soaking time T16 of 5 to 10 minutes. After the soaking is completed, take out the product and place it in an oven at a temperature T17 of 50° C. to 70° C. for drying;

[0025] During the drying process, the drying time T18 is controlled to be 30 to 60 minutes. After the drying time is completed, the coating thickness L is measured to be 0.1 to 0.3 mm.

[0026] Preferably, in step h), when applying a layer of bio-based protective film, the concentration M of the protective film solution ranges from 3 to 8%, the film thickness N after coating ranges from 0.05 to 0.1 mm, and satisfies the formula M×N≤0.4;

[0027] Prepare a bio-based protective film solution with a concentration M of 3 to 8%, and spray the solution evenly on the surface of the product treated in step g) by spraying; after spraying, control the drying temperature T19 to 50° C. to 70° C. to solidify the film layer; under the drying temperature condition, maintain the drying time T20 to 20 to 40 minutes;

[0028] After the drying time was complete, the film thickness N was measured to be between 0.05 and 0.1 mm.

[0029] Preferably, in step i), in the aging test, the light intensity I ranges from 500 to 1000 l ux, the humidity H ranges from 60 to 80%, and satisfies the formula I×H≤80000;

[0030] A light source with a light intensity I of 500 to 1000 l ux is placed on the coated product in step h); under the light condition, the ambient humidity H is controlled to be 60 to 80%; under the light and humidity conditions, the continuous exposure time T21 is 30 to 60 days;

[0031] After the medium exposure time, evaluate the change in physical properties of the product ΔP, where ΔP is the difference in physical properties before and after exposure. After the evaluation, place the sample in a biodegradable environment, control the temperature T22 to 25°C to 35°C, and maintain the humidity H unchanged, and monitor its degradation rate R, where R represents the percentage of mass loss per unit time.

[0032] Technical effects and advantages of the present invention: Compared with the prior art, the present invention provides a biodegradable and environmentally friendly plastic production process, which has the following advantages:

[0033] 1. Optimization of raw material ratio: By precisely controlling the weight ratio of polylactic acid (PLA) and corn starch, the final product achieves a balance between mechanical properties and biodegradability. Specifically, by controlling the weight ratio of polylactic acid and corn starch, both the mechanical strength of the material and its good biodegradability can be ensured.

[0034] 2. Improvement of plasticizer addition method: Adding a specific proportion of bio-based plasticizer to the mixture can not only improve the flexibility of the material, but also enhance its processing performance. By adjusting the proportion of plasticizer, its molding performance can be improved without sacrificing the degradability of the material.

[0035] 3. Extrusion granulation and injection molding parameter control: By finely controlling the temperature and pressure parameters during extrusion granulation and injection molding, it is possible to ensure that the material has a uniform structure and is free of defects during the molding process, thereby improving the stability and durability of the product.

[0036] 4. Surface modification: Using specific surface modification technology, such as spraying a specific concentration of modification liquid and drying it at an appropriate temperature, can significantly improve the weather resistance and anti-aging properties of the product and extend the service life of the product.

[0037] 5. Bio-based protective film coating: After surface modification, a thin layer of bio-based protective film is sprayed on the product to protect it from environmental factors without hindering its biodegradation process. This step ensures that the product has good stability during its service life and can be quickly degraded after disposal. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The present invention is a flow chart of the biodegradable and environmentally friendly plastic production process. DETAILED DESCRIPTION

[0039] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0040] The present invention provides a biodegradable environmentally friendly plastic production process, which optimizes the raw material ratio, improves the plasticizer addition method, strictly controls the temperature and pressure parameters of extrusion granulation and injection molding, and introduces efficient surface modification technology and bio-based protective film coating technology. The biodegradable environmentally friendly plastic prepared by the method of the present invention can ensure stability and durability during the service life, and can also quickly degrade after being discarded, reduce environmental pollution, and achieve better environmental protection effects.

[0041] Example 1

[0042] like Figure 1 As shown, the biodegradable and environmentally friendly plastic production process in this embodiment includes the following steps:

[0043] a) Raw material selection, selecting a mixture of polylactic acid and corn starch in a specific ratio; the further specific ratio is that the mass ratio of polylactic acid to corn starch is X:Y, wherein X is 60, Y is 40, and satisfies the formula X+Y=100;

[0044] The specific steps are as follows: before mixing the raw materials, preheat the polylactic acid to a temperature T1 of 50°C to 70°C. Preheating can improve the fluidity of the polylactic acid and facilitate subsequent mixing; the preheated polylactic acid is mixed with corn starch in a mass ratio of X:Y. The mixing should be carried out in a high-speed mixer to ensure that the raw materials are evenly dispersed; the mixture is kneaded through a twin-screw extruder, and the processing temperature of the extruder is set to T2, which is 170°C; during the mixing process, the screw speed S is controlled to remain at 30rpm.

[0045] By preheating the polylactic acid and mixing it in a high-speed mixer in a specific ratio, the uniform distribution of polylactic acid and corn starch is ensured, thereby improving the overall performance of the material. Setting the appropriate extrusion temperature T2 and screw speed S can ensure uniform melting and mixing of the material during the extrusion process, avoiding material decomposition caused by local overheating, and also ensuring the stability and consistency of the extrudate.

[0046] By controlling the mass ratio X:Y of polylactic acid to corn starch, the mechanical strength and toughness of the material can be improved while maintaining good biodegradability, so that it has better stability during its service life. Reasonable settings of preheating temperature T1 and screw speed S not only improve the processing performance of the material, but also improve production efficiency and reduce energy consumption. Through the above steps, the biodegradable and environmentally friendly plastic obtained achieves a good balance between mechanical properties and biodegradability, can maintain stable performance during its service life, and degrades rapidly after disposal, reducing environmental pollution.

[0047] Through the above specific implementation methods, the present invention effectively solves the problem in the prior art that it is difficult to balance the stability of materials during their service life and their degradation performance after disposal, and realizes a biodegradable and environmentally friendly plastic production process that is both environmentally friendly and practical.

[0048] b) uniformly mixing the polylactic acid and corn starch in a) according to a weight ratio; further, the weight ratio is a mass ratio of polylactic acid to corn starch Z:W, wherein Z is 60, W is 40, and satisfies the formula Z+W=100;

[0049] The specific steps are as follows: use a high-speed mixer to mix polylactic acid and corn starch at a speed R1 of 1000. High-speed mixing helps to increase the contact area between the raw materials and ensure that the two materials are evenly dispersed. During the mixing process, the duration is T3, which is 5 minutes. The longer mixing time helps to ensure that all particles can fully contact and mix evenly. After mixing, the mixture is cooled to room temperature T4, which does not exceed 25°C. Cooling can prevent the performance of the mixture from deteriorating or deteriorating due to high temperature. The cooled mixture is graded through a sieve with a sieve aperture D of 0.5 mm to remove large particles that are not mixed evenly. Sieve grading can ensure that there are no large unmixed particles in the final mixture and improve the consistency and uniformity of the material.

[0050] By using a high-speed mixer and mixing within the appropriate speed range, the uniform dispersion of polylactic acid and corn starch is ensured, improving the consistency of the material. This uniformity is critical for subsequent processing steps to avoid quality problems caused by uneven mixing.

[0051] The mechanical properties of the material can be optimized by controlling the mass ratio of polylactic acid to corn starch Z:W to 60:40. Polylactic acid provides good mechanical strength, while corn starch increases the biodegradability of the material. Temperature control during mixing (cooling to room temperature T4 not exceeding 25°C) helps prevent the material from changing properties or deteriorating at high temperatures, ensuring the stability and reliability of the material in subsequent processing.

[0052] By sieving, large particles that are not mixed evenly can be removed, further improving the uniformity and consistency of the material. This helps to avoid defects caused by uneven particles in subsequent processing, such as gaps or cracks during molding.

[0053] Through the above specific implementation methods, the present invention effectively solves the problem of uneven material mixing in the prior art, ensures the stability of the final product during its service life and its degradation performance after disposal, and realizes a biodegradable and environmentally friendly plastic production process that is both environmentally friendly and practical.

[0054] c) adding a specific proportion of a bio-based plasticizer to the mixture in b), wherein the amount of the plasticizer added directly affects the flexibility and processing properties of the material; further, the specific proportion is a weight ratio of the bio-based plasticizer to the mixture A:B, wherein A is 5, B is 95, and satisfies the formula A+B=100;

[0055] The specific steps are: add a bio-based plasticizer in a weight ratio of A:B to the mixture, where A is in the range of 5, and then heat it at a temperature T5, which helps the plasticizer to be evenly distributed in the mixture, thereby improving the flexibility of the material. T5 is 60°C; during the heating process, continue stirring for a time T6, which is 10 minutes, until the plasticizer is completely integrated into the mixture. Continuous stirring helps the plasticizer to be evenly dispersed throughout the mixture to avoid local aggregation; after completion, cool the resulting mixture to room temperature T7, which does not exceed 25°C. Cooling can ensure the stability and consistency of the material in subsequent processing.

[0056] By adding a specific proportion of bio-based plasticizers, the flexibility of the material can be significantly improved, making the final product less likely to break during use and enhancing its durability. During the heating and stirring process, the plasticizer is evenly distributed in the mixture, improving the fluidity and processing performance of the material. This helps to achieve better molding results in the subsequent extrusion granulation and injection molding processes. By heating at a specific temperature T5 and continuing the stirring time T6, it can be ensured that the plasticizer is completely integrated into the mixture to avoid degradation of material properties due to insufficient or excessive heating. Continuous stirring and cooling treatment (cooling to room temperature T7 not exceeding 25°C) can further improve the uniformity and consistency of the material and avoid quality problems caused by uneven distribution of plasticizers.

[0057] Through the above specific implementation methods, the present invention effectively solves the problem of uneven addition of plasticizers in the prior art, ensures the stability of the final product during its service life and its degradation performance after disposal, and realizes a biodegradable and environmentally friendly plastic production process that is both environmentally friendly and practical.

[0058] d) extruding and granulating the mixture in c); further, during the extrusion granulation process, the extruder screw speed V is 20 rpm, the extrusion temperature T8 is in the range of 170° C., and the formula T8-T9≥20° C. is satisfied, wherein T9 is the cooling section temperature;

[0059] The specific steps are as follows: feed the mixture in d) into the extruder, set the screw speed V to 20rpm, and the moderate screw speed can ensure that the material is evenly stressed during the extrusion process, avoiding uneven or overheating of the material caused by too high or too low speed; during the extrusion process, control the extrusion temperature T8 to be maintained at 170°C, and the higher extrusion temperature helps the material to fully melt, improve its fluidity and uniformity, and thus obtain a consistent extrusion effect; under the extrusion temperature condition, ensure that the cooling section temperature T9 is at least 20°C lower than T8, and the appropriate cooling section temperature can quickly solidify the extruded material to prevent it from deforming or sticking during subsequent processing; after completion, pelletize the extruded strip material to obtain particles with a particle size D1 of 2 mm. Uniform particle size helps subsequent injection molding and other processing steps to improve the quality and consistency of the finished product.

[0060] By setting the screw speed V to 20rpm, the material is uniformly stressed during the extrusion process, avoiding shear damage to the material due to too high a speed or incomplete melting of the material due to too low a speed. Controlling the extrusion temperature T8 to 170°C can ensure that the material is fully melted during the extrusion process and improve its fluidity and uniformity. This helps to achieve consistent extrusion results and reduce material defects caused by improper temperature control. By ensuring that the cooling section temperature T9 is at least 20°C lower than T8, the extruded material can be quickly solidified to prevent deformation or adhesion during subsequent processing. This helps to improve the stability and consistency of the extruded material. Pellets with a particle size D1 of 2 mm are obtained by pelletizing, which can ensure uniformity and consistency in subsequent processing steps. Uniform particle size is also conducive to improving the processing performance of subsequent processes such as injection molding.

[0061] Through the above specific implementation methods, the present invention effectively solves the problems of uneven force and poor melting of materials in the extrusion granulation process in the prior art, ensures the stability of the final product during its service life and its degradation performance after disposal, and realizes an environmentally friendly and practical biodegradable environmentally friendly plastic production process.

[0062] e) injection molding the particles obtained in d) into a desired shape; further, during the injection molding, the mold temperature T10 is 40° C., the injection pressure P1 is in the range of 60 MPa, and the formula P1×T10≤4500 is satisfied;

[0063] The specific steps are as follows: put the pellets into the injection molding machine and set the mold temperature T10 to 40°C. The appropriate mold temperature helps the material to flow and form evenly in the mold. Set the injection pressure P1 to 60. A higher injection pressure can ensure that the material can quickly fill the mold and improve the density and surface quality of the molded part. Under the injection pressure condition, control the holding time T11 to 10 seconds. The control of the holding time helps to ensure that the material is fully compacted in the mold and reduce internal voids and surface defects. After completion, cool the product to room temperature T12, T12 does not exceed 25°C, to complete the molding. Cooling can ensure that the product has sufficient hardness when demolding to avoid deformation caused by excessive temperature.

[0064] By controlling the mold temperature T10 to 40°C, it is possible to ensure that the material flows evenly in the mold and avoid molding defects caused by too high or too low temperature. Appropriate mold temperature helps to improve the surface finish and dimensional accuracy of the molded parts. By setting the injection pressure P1 to 60MPa and satisfying the formula P1×T10≤4500, it is possible to ensure that the material quickly fills the mold under high pressure and improves the density of the molded parts. This helps to reduce internal voids and improve the mechanical properties of the product. By controlling the holding time T11 to 10 seconds, it is possible to ensure that the material is fully compacted in the mold and reduce internal voids and surface defects. Appropriate holding time helps to improve the uniformity and stability of the product. By cooling the molded product to room temperature T12, T12 does not exceed 25°C, it is possible to ensure that the product has sufficient hardness when demolding to avoid deformation or damage caused by excessive temperature. The cooling process can also reduce the internal stress of the product and improve its long-term stability.

[0065] f) controlling the temperature and pressure parameters during the molding process of e); further, in the controlled temperature and pressure parameters, the mold temperature T13 ranges to 40°C, the injection pressure P2 ranges to 60, and the formula T13×P2≤4800 is satisfied;

[0066] The specific steps are: during the molding process, set the mold temperature T13 to 40°C. Appropriate mold temperature can ensure uniform flow and filling of the material in the mold, avoid molding defects caused by too high or too low temperature, and set the injection pressure P2 to 60; under the injection pressure condition, control the holding time T14 to 10; during the holding time, ensure that the cooling water flow F1 is 1 liter / minute; under the cooling water flow condition, wait for the product to cool to room temperature T15, T15 does not exceed 25°C, to complete the molding.

[0067] By controlling the mold temperature T13 to 40°C, it is possible to ensure that the material flows and fills evenly in the mold, avoiding molding defects caused by too high or too low temperature. Appropriate mold temperature helps improve the surface finish and dimensional accuracy of the molded parts.

[0068] By setting the injection pressure P2 to 60MPa and satisfying the formula T13×P2≤4800, it is possible to ensure that the material quickly fills the mold under high pressure and improve the density of the molded part. This helps reduce internal voids and improve the mechanical properties of the product.

[0069] By controlling the holding time T14 to 10 seconds, it can ensure that the material is fully compacted in the mold, reducing internal voids and surface defects. Appropriate holding time helps improve the uniformity and stability of the product.

[0070] By controlling the cooling water flow rate F1 to 1 liter / minute, it is possible to ensure that the material dissipates heat quickly in the mold, avoiding deformation or defects caused by insufficient cooling. This helps to improve the dimensional stability and surface quality of the product.

[0071] By cooling the molded product to room temperature T15, which does not exceed 25°C, it can ensure that the product has sufficient hardness when demoulding to avoid deformation or damage caused by excessive temperature. The cooling process can also reduce the internal stress of the product and improve its long-term stability.

[0072] Through the above specific implementation methods, the present invention effectively solves the problems of uneven material flow, internal voids in molded parts, surface defects, etc. in the injection molding process in the prior art, ensures the stability of the final product during its service life and its degradation performance after disposal, and realizes an environmentally friendly and practical biodegradable environmentally friendly plastic production process.

[0073] g) performing surface modification treatment on the product prepared in f) to enhance its weather resistance; further, in the surface modification treatment, the coating thickness L is 0.1 mm, the coating liquid concentration C is 510%, and the formula C×L≤3 is satisfied;

[0074] The specific steps are as follows: prepare a coating liquid with a concentration C of 5 for the surface treatment of the product in g). The appropriate coating liquid concentration can ensure that the coating is evenly distributed on the surface of the product and enhance its weather resistance; immerse the product prepared in the coating liquid for an immersion time T16 of 5 minutes. During the immersion time, ensure that the surface of the product fully absorbs the coating liquid to form a uniform coating. After the immersion is completed, take out the product and place it in an oven at a temperature T17 of 50°C for drying. The appropriate drying temperature can accelerate the curing of the coating and prevent the coating from falling off in subsequent treatments; during the drying process, control the drying time T18 to 30 minutes. The appropriate drying time can ensure that the coating is completely cured to form a solid surface layer. After the drying time is over, the coating thickness L is measured to be 0.1 mm. By controlling the coating thickness, it can be ensured that the product surface has good weather resistance and extend its service life.

[0075] By forming a coating with a thickness of 0.1 mm on the surface of the product, the weather resistance of the product can be significantly improved. This coating can resist environmental factors such as ultraviolet radiation and moisture erosion, and extend the service life of the product. By controlling the coating liquid concentration C to 5, it can be ensured that the coating is evenly distributed on the surface of the product, avoiding unevenness or shedding caused by too high or too low coating liquid concentration. The appropriate concentration helps to improve the adhesion and stability of the coating. By setting the immersion time T16 to 5, it can be ensured that the coating liquid is fully absorbed by the surface of the product to form a uniform coating. This helps to improve the appearance quality and durability of the product. By drying in an oven at a temperature T17 of 50°C, the curing process of the coating can be accelerated and the softening or shedding of the coating caused by insufficient curing can be reduced. The appropriate drying temperature helps to improve the stability and durability of the coating. By controlling the drying time T18 to 30 minutes, it can be ensured that the coating is fully cured to form a solid surface layer. This helps to improve the surface hardness and wear resistance of the product.

[0076] Through the above specific implementation methods, the present invention effectively solves the problems of uneven coating and poor weather resistance in the surface modification process in the prior art, ensures the stability of the final product during its service life and its degradation performance after disposal, and realizes a biodegradable and environmentally friendly plastic production process that is both environmentally friendly and practical.

[0077] h) coating a layer of bio-based protective film on the surface of the product treated in g); further, in coating the layer of bio-based protective film, the concentration M of the protective film solution is in the range of 3%, the thickness N of the film after coating is in the range of 0.05 mm, and the formula M×N≤0.4 is satisfied;

[0078] The specific steps are as follows: prepare a bio-based protective film solution with a concentration M of 3%. The appropriate solution concentration can ensure that the film layer is evenly distributed on the product surface to form a stable protective layer. Use a spraying method to evenly spray the solution on the surface of the product treated in step g). When spraying, ensure that the nozzle is appropriately away from the product surface to form a uniform film layer; after spraying, control the drying temperature T19 to 50°C to solidify the film layer; under the drying temperature condition, maintain the drying time T20 to 20 minutes; after the drying time is over, measure the film thickness N to be 0.05 mm. By controlling the film thickness, it can be ensured that the product surface has good protective performance.

[0079] By coating a 0.05 mm thick bio-based protective film on the surface of the product, the surface protection performance of the product can be significantly improved. This film can resist the influence of external environmental factors, such as ultraviolet rays, water erosion, etc., and extend the service life of the product. By controlling the concentration M of the protective film solution to 3%, it can ensure that the film layer is evenly distributed on the surface of the product, avoiding uneven film layer or shedding caused by too high or too low solution concentration. The appropriate solution concentration helps to improve the adhesion and stability of the film layer.

[0080] By spraying the solution evenly on the product surface, the film layer can be evenly distributed on the product surface. This helps to improve the appearance quality and surface protection performance of the product. By drying at a drying temperature T19 of 50°C, the curing process of the film layer can be accelerated and the softening or shedding of the film layer caused by insufficient curing can be reduced. The appropriate drying temperature helps to improve the stability and durability of the film layer. By controlling the drying time T20 to 20 minutes, it can be ensured that the film layer is completely cured to form a solid protective layer. This helps to improve the surface hardness and wear resistance of the product.

[0081] i) performing an aging test on the coated product in h) to verify its stability during use and degradation performance after disposal; further, in the aging test, the light intensity I ranges from 500 lux to 60% of the humidity H, and the formula I×H≤80000 is satisfied;

[0082] The specific steps are: placing a light source with a light intensity of 500 lux on the coated product in step h), and the appropriate light intensity can simulate the sunlight conditions in the natural environment to test the weather resistance of the product; under the light conditions, the environmental humidity H is controlled to be 60%; under the light and humidity conditions, the continuous exposure time T21 is 30 days, and the longer exposure time can simulate the long-term use of the product in the natural environment to evaluate its durability; after the exposure time, evaluate the physical property change ΔP of the product, ΔP is the difference in physical properties before and after exposure; after the evaluation, place the sample in a biodegradable environment, control the temperature T22 to 25°C, maintain the humidity H unchanged, and monitor its degradation rate R, R represents the percentage of mass loss per unit time. By monitoring the degradation rate, the biodegradability of the product can be evaluated.

[0083] By conducting an aging test under the conditions of 500 lux of light intensity I and 60% of humidity H, the weather resistance of the product during its service life can be verified. Appropriate light and humidity conditions can simulate the sunlight and humidity in the natural environment, ensuring that the product has good stability and durability when used outdoors.

[0084] By evaluating the change in physical properties of the product before and after exposure, ΔP, the performance changes of the product under light and humidity conditions can be quantified. This helps to identify the performance degradation that may occur during the service life of the product and take corresponding measures to improve it.

[0085] By controlling the light intensity I and humidity H and satisfying the formula I×H≤80000, the rationality of the test conditions can be ensured to avoid deviations in test results caused by overly harsh or loose conditions. Appropriate test conditions help to accurately evaluate the weather resistance of products.

[0086] The biodegradability of the product can be verified by monitoring the degradation rate R in a biodegradation environment with a temperature T22 of 25°C and a constant humidity H. This helps ensure that the product can be rapidly degraded after disposal, reducing environmental pollution.

[0087] Example 2

[0088] A biodegradable and environment-friendly plastic production process comprises: a) selecting raw materials, selecting a mixture of polylactic acid and corn starch in a specific ratio; b) uniformly mixing the polylactic acid and corn starch in a) according to a weight ratio; c) adding a specific ratio of a bio-based plasticizer to the mixture in b); d) extruding and granulating the mixture in c); e) injection molding the particles obtained in d) into a desired shape; f) controlling temperature and pressure parameters during the molding process in e); g) performing surface modification treatment on the product prepared in f) to enhance its weather resistance; h) coating a layer of bio-based protective film on the surface of the product treated in g); i) performing an aging test on the coated product in h) to verify its stability during service life and degradation performance after disposal.

[0089] Preferably, in step a), the specific ratio is a mass ratio of polylactic acid to corn starch of X:Y, wherein X is 80, Y is 20, and the formula X+Y=100 is satisfied;

[0090] Before mixing the raw materials, the polylactic acid is preheated to a temperature T1, T1 being 70°C; the preheated polylactic acid is mixed with corn starch in a mass ratio of X:Y; the mixture is kneaded through a twin-screw extruder, and the processing temperature of the extruder is set to T2, T2 being 190°C; during the kneading process, the screw speed S is controlled to be maintained at 50rpm.

[0091] Preferably, in step b), the weight ratio is the mass ratio of polylactic acid to corn starch Z:W, wherein Z is 80, W is 20, and satisfies the formula Z+W=100;

[0092] The polylactic acid and corn starch are mixed by a high-speed mixer at a rotation speed R1 of 1500 rpm. During the mixing process, the duration is T3, and T3 is 10 minutes.

[0093] After the mixing is completed, the mixture is cooled to room temperature T4, T4 not exceeding 25°C; the cooled mixture is graded through a sieve with an aperture D of 1.0 mm to remove large particles that are not mixed uniformly.

[0094] Preferably, in step c), the specific ratio is a weight ratio of the bio-based plasticizer to the mixture A:B, wherein A is 15, B is 85, and satisfies the formula A+B=100;

[0095] Adding a bio-based plasticizer in a weight ratio of A:B to the mixture, where A is in the range of 15, and then heating it at a temperature T5, where T5 is 80°C;

[0096] During the heating process, the stirring time T6 is continued, T6 is 20 minutes, until the plasticizer is completely integrated into the mixture; after completion, the obtained mixture is cooled to room temperature T7, T7 does not exceed 25°C.

[0097] Preferably, in step d), during the extrusion granulation process, the extruder screw speed V is 40 rpm, the extrusion temperature T8 is 190° C., and the formula T8-T9≥20° C. is satisfied, wherein T9 is the cooling section temperature;

[0098] The mixture in d) is fed into the extruder, and the screw speed V is set to 40 rpm; during the extrusion process, the extrusion temperature T8 is controlled to be maintained at 190° C.; under the extrusion temperature condition, it is ensured that the cooling section temperature T9 is at least 20° C. lower than T8; after completion, the extruded strip material is pelletized to obtain particles with a particle size D1 of 5 mm.

[0099] Preferably, in step e), during injection molding, the mold temperature T10 is in the range of 60° C., the injection pressure P1 is in the range of 80 MPa, and the formula P1×T10≤4500 is satisfied;

[0100] Put the pellets into the injection molding machine, set the mold temperature T10 to 60℃, and set the injection pressure P1 to 80MPa; under the injection pressure condition, control the holding time T11 to 30 seconds; after completion, cool the product to room temperature T12, T12 does not exceed 25℃, to complete the molding.

[0101] Preferably, in step f), the temperature and pressure parameters are controlled such that the mold temperature T13 is 60° C., the injection pressure P2 is 80 MPa, and the formula T13×P2≤4800 is satisfied;

[0102] During the molding process, the mold temperature T13 was set to 60°C and the injection pressure P2 was set to 80MPa;

[0103] Under the injection pressure condition, control the holding time T14 to 30 seconds; during the holding time, ensure that the cooling water flow F1 is 2 liters / minute; under the cooling water flow condition, wait for the product to cool to room temperature T15, T15 does not exceed 25°C, to complete the molding.

[0104] Preferably, in g), in the surface modification treatment, the coating thickness L is 0.3 mm, the coating liquid concentration C is 10%, and the formula C×L≤3 is satisfied;

[0105] Prepare a coating liquid with a concentration C of 10% for surface treatment of the product in g);

[0106] Immerse the product prepared in the above into the coating liquid for a soaking time T16 of 5 to 10 minutes. After the soaking is completed, take out the product and place it in an oven at a temperature T17 of 70° C. to dry;

[0107] During the drying process, the drying time T18 was controlled to be 60 minutes. After the drying time was completed, the coating thickness L was measured to be 0.3 mm.

[0108] Preferably, in step h), when applying a layer of bio-based protective film, the concentration M of the protective film solution is 8%, the film thickness N after coating is 0.1 mm, and the formula M×N≤0.4 is satisfied;

[0109] Prepare a bio-based protective film solution with a concentration M of 8%, and spray the solution evenly on the surface of the product treated in step g) by spraying; after spraying, control the drying temperature T19 to 70° C. to solidify the film layer; under the drying temperature condition, maintain the drying time T20 to 40 minutes;

[0110] After the drying time was over, the film thickness N was measured to be 0.1 mm.

[0111] Preferably, in step i), in the aging test, the light intensity I is 1000 l ux, the humidity H is 80%, and the formula I×H≤80000 is satisfied;

[0112] A light source with a light intensity I of 1000 lux is placed on the coated product in step h); under the light condition, the ambient humidity H is controlled to be 80%; under the light and humidity conditions, the continuous exposure time T21 is 60 days;

[0113] After the exposure time, the physical property change ΔP of the product is evaluated. ΔP is the difference in physical properties before and after exposure. After the evaluation, the sample is placed in a biodegradable environment, the temperature T22 is controlled at 35°C, the humidity H is maintained unchanged, and its degradation rate R is monitored. R represents the percentage of mass loss per unit time.

[0114] Example 3

[0115] A biodegradable and environment-friendly plastic production process comprises: a) selecting raw materials, selecting a mixture of polylactic acid and corn starch in a specific ratio; b) uniformly mixing the polylactic acid and corn starch in a) according to a weight ratio; c) adding a specific ratio of a bio-based plasticizer to the mixture in b); d) extruding and granulating the mixture in c); e) injection molding the particles obtained in d) into a desired shape; f) controlling temperature and pressure parameters during the molding process in e); g) performing surface modification treatment on the product prepared in f) to enhance its weather resistance; h) coating a layer of bio-based protective film on the surface of the product treated in g); i) performing an aging test on the coated product in h) to verify its stability during service life and degradation performance after disposal.

[0116] Preferably, in step a), the specific ratio is a mass ratio of polylactic acid to corn starch of X:Y, wherein X is 70, Y is 30, and the formula X+Y=100 is satisfied;

[0117] Before mixing the raw materials, the polylactic acid is preheated to a temperature T1, T1 being 60°C; the preheated polylactic acid is mixed with corn starch in a mass ratio of X:Y; the mixture is kneaded through a twin-screw extruder, and the processing temperature of the extruder is set to T2, T2 being 180°C; during the kneading process, the screw speed S is controlled to be maintained at 40rpm.

[0118] Preferably, in step b), the weight ratio is the mass ratio of polylactic acid to corn starch Z:W, wherein Z is in the range of 70, W is in the range of 30, and satisfies the formula Z+W=100;

[0119] The polylactic acid and corn starch are mixed by a high-speed mixer at a rotation speed R1 of 1200 rpm. During the mixing process, the duration is T3, and T3 is 7 minutes.

[0120] After the mixing is completed, the mixture is cooled to room temperature T4, T4 not exceeding 25°C; the cooled mixture is graded through a sieve with an aperture D of 0.7 mm to remove large particles that are not mixed uniformly.

[0121] Preferably, in step c), the specific ratio is a weight ratio of the bio-based plasticizer to the mixture A:B, wherein A is 10, B is 90, and satisfies the formula A+B=100;

[0122] Adding a bio-based plasticizer in a weight ratio of A:B to the mixture, where A is in the range of 10, and then heating it at a temperature T5, where T5 is 70°C;

[0123] During the heating process, the stirring time T6 is continued, T6 is 15 minutes, until the plasticizer is completely integrated into the mixture; after completion, the obtained mixture is cooled to room temperature T7, T7 does not exceed 25°C.

[0124] Preferably, in step d), during the extrusion granulation process, the extruder screw speed V is in the range of 30 rpm, the extrusion temperature T8 is in the range of 180° C., and the formula T8-T9≥20° C. is satisfied, wherein T9 is the cooling section temperature;

[0125] The mixture in d) is fed into the extruder, and the screw speed V is set to 30 rpm; during the extrusion process, the extrusion temperature T8 is controlled to be maintained at 180° C.; under the extrusion temperature condition, it is ensured that the cooling section temperature T9 is at least 20° C. lower than T8; after completion, the extruded strip material is pelletized to obtain particles with a particle size D1 of 3 mm.

[0126] Preferably, in step e), during injection molding, the mold temperature T10 is in the range of 50° C., the injection pressure P1 is in the range of 70 MPa, and the formula P1×T10≤4500 is satisfied;

[0127] Put the pellets into the injection molding machine, set the mold temperature T10 to 50℃, and set the injection pressure P1 to 70MPa; under the injection pressure condition, control the holding time T11 to 20 seconds; after completion, cool the product to room temperature T12, T12 does not exceed 25℃, to complete the molding.

[0128] Preferably, in step f), the temperature and pressure parameters are controlled such that the mold temperature T13 is in the range of 50°C, the injection pressure P2 is in the range of 70MPa, and the formula T13×P2≤4800 is satisfied;

[0129] During the molding process, the mold temperature T13 was set to 50°C and the injection pressure P2 was set to 70MPa;

[0130] Under the injection pressure condition, control the holding time T14 to 20 seconds; during the holding time, ensure that the cooling water flow F1 is 2 liters / minute; under the cooling water flow condition, wait for the product to cool to room temperature T15, T15 does not exceed 25°C to complete the molding.

[0131] Preferably, in g), in the surface modification treatment, the coating thickness L is in the range of 0.2 mm, the coating liquid concentration C is in the range of 7%, and the formula C×L≤3 is satisfied;

[0132] Prepare a coating liquid with a concentration C of 7% for surface treatment of the product in g);

[0133] The product prepared in the above step is immersed in the coating liquid for 7 minutes. After the immersion is completed, the product is taken out and placed in an oven at a temperature T17 of 60° C. for drying.

[0134] During the drying process, the drying time T18 was controlled to be 40 minutes. After the drying time was over, the coating thickness L was measured to be 0.2 mm.

[0135] Preferably, in step h), when applying a layer of bio-based protective film, the concentration M of the protective film solution is in the range of 5%, the film thickness N after coating is in the range of 0.07 mm, and the formula M×N≤0.4 is satisfied;

[0136] Prepare a bio-based protective film solution with a concentration M of 5%, and spray the solution evenly on the surface of the product treated in step g) by spraying; after spraying, control the drying temperature T19 to 60° C. to solidify the film layer; under the drying temperature condition, maintain the drying time T20 to 30 minutes;

[0137] After the drying time was over, the film thickness N was measured to be 0.07 mm.

[0138] Preferably, in step i), in the aging test, the light intensity I is in the range of 700 l ux, the humidity H is in the range of 70%, and the formula I×H≤80000 is satisfied;

[0139] A light source with a light intensity I of 700 lux is placed on the coated product in step h); under the light condition, the ambient humidity H is controlled to be 70%; under the light and humidity conditions, the continuous exposure time T21 is 50 days;

[0140] After the medium exposure time, the physical property change ΔP of the product is evaluated, where ΔP is the difference in physical properties before and after exposure. After the evaluation, the sample is placed in a biodegradable environment, the temperature T22 is controlled at 30°C, the humidity H is maintained unchanged, and its degradation rate R is monitored, where R represents the percentage of mass loss per unit time.

[0141] In order to verify the effectiveness of the biodegradable and environmentally friendly plastic production process of the present invention, we conducted detailed experimental records and summarized the experimental data as follows:

[0142] 1. Raw material ratio:

[0143] The mass ratio of polylactic acid (PLA) to corn starch is 70:30.

[0144] 2. Preheating and mixing:

[0145] Polylactic acid preheating temperature T1: 60℃.

[0146] High speed mixer speed R1: 1200rpm.

[0147] Mixing time T3: 8 minutes.

[0148] The temperature of the cooled mixture T4: 23°C.

[0149] Screen aperture D: 0.8 mm.

[0150] 3. Plasticizer addition:

[0151] The weight ratio of bio-based plasticizer to the mixture is A:B:10:90.

[0152] Heating temperature T5: 70℃.

[0153] Stirring time T6: 15 minutes.

[0154] The temperature of the cooled mixture T7: 23°C.

[0155] 4. Extrusion granulation:

[0156] Screw speed V: 30rpm.

[0157] Extrusion temperature T8: 180°C. Cooling section temperature T9: 160°C. Particle size D1: 3 mm.

[0158] 5. Injection molding:

[0159] Mold temperature T10: 50°C. Injection pressure P1: 70MPa. Holding time T11: 20 seconds. Room temperature T12: 22°C.

[0160] 6. Surface modification:

[0161] Coating liquid concentration C: 7%.

[0162] Soaking time T16: 8 minutes. Oven drying temperature T17: 60°C. Drying time T18: 45 minutes. Coating thickness L: 0.2 mm.

[0163] 7. Bio-based protective film coating: protective film solution concentration M: 5%.

[0164] Drying temperature T19: 60°C. Drying time T20: 30 minutes. Film thickness N: 0.07 mm.

[0165] 8. Aging test:

[0166] Light intensity I: 800 lux. Ambient humidity H: 70%.

[0167] Exposure time T21: 45 days. Physical property change ΔP: 10%. Temperature T22: 30°C.

[0168] Degradation rate R: 2% / week.

[0169] Comparative data

[0170] In order to compare the effects of the process of the present invention with the traditional process, we also recorded the data of the comparative example: 1. Raw material ratio:

[0171] The mass ratio of polylactic acid (PLA) to corn starch: 70:30. (Same as the experimental group)

[0172] 2. Preheating and mixing:

[0173] Polylactic acid preheating temperature T1: not preheated.

[0174] High speed mixer speed R1: 800rpm.

[0175] Mixing time T3: 5 minutes.

[0176] The temperature of the cooled mixture T4: 25°C (same as the experimental group)

[0177] Screen aperture D: No screen was used.

[0178] 3. Plasticizer addition:

[0179] Weight ratio of bio-based plasticizer to mixture A:B: No plasticizer added.

[0180] 4. Extrusion granulation:

[0181] Screw speed V: 20rpm.

[0182] Extrusion temperature T8: 160°C.

[0183] Cooling section temperature T9: 140℃.

[0184] Particle size D1: 4 mm.

[0185] 5. Injection molding:

[0186] Mould temperature T10: 40℃.

[0187] Injection pressure P1: 60MPa.

[0188] Holding time T11: 10 seconds.

[0189] Room temperature T12: 22℃. (Same as the experimental group)

[0190] 6. Surface modification:

[0191] Coating liquid concentration C: No surface modification treatment was performed.

[0192] Bio-based protective film coating:

[0193] Concentration M of protective film solution: No coating treatment was performed.

[0194] 7. Aging test:

[0195] Light intensity I: 800 l ux. (Same as the experimental group)

[0196] Ambient humidity H: 70%. (Same as the experimental group)

[0197] Exposure time T21: 45 days. (Same as the experimental group)

[0198] Physical property change ΔP: 25%. (Significantly greater than the experimental group)

[0199] Temperature T22: 30℃. (Same as the experimental group)

[0200] Degradation rate R: 0.5% / week. (Significantly lower than the experimental group)

[0201] Contrast effect

[0202] By comparing the data of the experimental group and the control group, we can draw the following conclusions:

[0203] Changes in physical properties:

[0204] The physical property change ΔP of the experimental group was 10%, while the physical property change ΔP of the comparative example reached 25%. This shows that the process of the present invention has obvious advantages in improving the physical stability of the product.

[0205] Degradation rate:

[0206] The degradation rate R of the experimental group was 2% / week, while the degradation rate R of the comparative group was only 0.5% / week. This shows that the process of the present invention also has obvious advantages in improving the biodegradability of the product.

[0207] Processing performance and consistency:

[0208] In the process of extrusion granulation and injection molding, the experimental group adopted optimized processing parameters (such as screw speed, extrusion temperature, etc.), so the particle size of the particles was more uniform and the quality of the finished product was higher. However, due to the lack of these optimization measures, the quality of the finished product of the comparative group was lower.

[0209] Surface modification and protective film coating:

[0210] The experimental group underwent surface modification and bio-based protective film coating to improve the weather resistance and anti-aging performance of the product. However, the control group did not undergo these treatments, resulting in a more obvious performance degradation in the aging test.

[0211] In summary, the biodegradable and environmentally friendly plastic production process provided by the present invention has significant improvements in terms of physical property stability, biodegradability and processing performance of the product, and has obvious advantages.

[0212] Comprehensive evaluation of stability and degradation performance: By combining weathering tests and biodegradation performance monitoring, the stability of the product during its service life and its degradation performance after disposal can be comprehensively evaluated. This helps to ensure the reliability and environmental friendliness of the product in practical applications.

[0213] Finally, it should be noted that the above are only preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A biodegradable and environmentally friendly plastic production process, characterized in that: include: a) selecting raw materials, selecting a mixture of polylactic acid and corn starch in a specific ratio; b) uniformly mixing the polylactic acid and corn starch in a) according to a weight ratio; c) adding a specific proportion of a bio-based plasticizer to the mixture in b); d) subjecting the mixture in c) to extrusion granulation; e) subjecting the granules obtained in d) to injection molding to prepare a desired shape; f) controlling temperature and pressure parameters during the molding process in e); g) subjecting the product prepared in f) to surface modification to enhance its weather resistance; h) coating a bio-based protective film on the surface of the product treated in g); i) conducting an aging test on the coated product in h) to verify its stability during service life and its degradation performance after disposal.

2. A biodegradable and environmentally friendly plastic production process according to claim 1, characterized in that: In step a), the specific ratio is that the mass ratio of polylactic acid to corn starch is X:Y, wherein X ranges from 60 to 80, Y ranges from 20 to 40, and satisfies the formula X+Y=100; Before mixing the raw materials, the polylactic acid is preheated to a temperature T1 of 50°C to 70°C; the preheated polylactic acid is mixed with corn starch in a mass ratio of X:Y; the mixture is kneaded through a twin-screw extruder, and the processing temperature of the extruder is set to T2 of 170°C to 190°C; during the kneading process, the screw speed S is controlled to remain at 30 to 50rpm.

3. A biodegradable and environmentally friendly plastic production process according to claim 2, characterized in that: In step b), the weight ratio is the mass ratio of polylactic acid to corn starch Z:W, wherein Z ranges from 60 to 80, W ranges from 20 to 40, and satisfies the formula Z+W=100; Using a high-speed mixer, polylactic acid and corn starch are mixed at a rotation speed R1 of 1000 to 1500 rpm. During the mixing process, the duration is T3, and T3 is 5 to 10 minutes; After the mixing is completed, the mixture is cooled to room temperature T4, T4 not exceeding 25°C; the cooled mixture is graded through a sieve with an aperture D of 0.5 to 1.0 mm to remove large particles that are not mixed uniformly.

4. A biodegradable and environmentally friendly plastic production process according to claim 3, characterized in that: In step c), the specific ratio is a weight ratio of the bio-based plasticizer to the mixture A:B, wherein A ranges from 5 to 15, B ranges from 85 to 95, and satisfies the formula A+B=100; Adding a bio-based plasticizer in a weight ratio of A:B to the mixture, wherein A ranges from 5 to 15, and then heating the mixture at a temperature T5, wherein T5 ranges from 60°C to 80°C; During the heating process, the stirring time T6 is continued, T6 is 10 to 20 minutes, until the plasticizer is completely integrated into the mixture; after completion, the obtained mixture is cooled to room temperature T7, T7 does not exceed 25°C.

5. A biodegradable and environmentally friendly plastic production process according to claim 4, characterized in that: In step d), during the extrusion granulation process, the extruder screw speed V ranges from 20 to 40 rpm, the extrusion temperature T8 ranges from 170° C. to 190° C., and satisfies the formula T8-T9≥20° C., where T9 is the cooling section temperature; The mixture in d) is fed into an extruder, and the screw speed V is set to 20 to 40 rpm; during the extrusion process, the extrusion temperature T8 is controlled to be maintained at 170° C. to 190° C.; under the extrusion temperature condition, it is ensured that the cooling section temperature T9 is at least 20° C. lower than T8; after completion, the extruded strip material is pelletized to obtain particles with a particle size D1 of 2 to 5 mm.

6. A biodegradable and environmentally friendly plastic production process according to claim 5, characterized in that: In step e), during injection molding, the mold temperature T10 ranges from 40° C. to 60° C., the injection pressure P1 ranges from 60 to 80 MPa, and satisfies the formula P1×T10≤4500; Put the pellets into the injection molding machine, set the mold temperature T10 to 40℃ to 60℃, and set the injection pressure P1 to 60 to 80MPa; under the injection pressure condition, control the holding time T11 to 10 to 30 seconds; after completion, cool the product to room temperature T12, T12 not exceeding 25℃, to complete the molding.

7. A process for producing biodegradable and environmentally friendly plastics according to claim 6, characterized in that: In step f), the temperature and pressure parameters are controlled such that the mold temperature T13 ranges from 40° C. to 60° C., the injection pressure P2 ranges from 60 to 80 MPa, and the formula T13×P2≤4800 is satisfied; During the molding process, the mold temperature T13 is set to 40°C to 60°C, and the injection pressure P2 is set to 60 to 80 MPa; Under the injection pressure condition, control the holding time T14 to 10 to 30 seconds; during the holding time, ensure that the cooling water flow F1 is 1 to 2 liters / minute; under the cooling water flow condition, wait for the product to cool to room temperature T15, T15 does not exceed 25°C to complete the molding.

8. A process for producing biodegradable and environmentally friendly plastics according to claim 7, characterized in that: In g), in the surface modification treatment, the coating thickness L ranges from 0.1 to 0.3 mm, the coating liquid concentration C ranges from 5 to 10%, and satisfies the formula C×L≤3; Preparing a coating liquid with a concentration C of 5 to 10% for surface treatment of the product in g); Immerse the product prepared in the above into the coating liquid for a soaking time T16 of 5 to 10 minutes. After the soaking is completed, take out the product and place it in an oven at a temperature T17 of 50° C. to 70° C. for drying; During the drying process, the drying time T18 is controlled to be 30 to 60 minutes. After the drying time is completed, the coating thickness L is measured to be 0.1 to 0.3 mm.

9. A biodegradable and environmentally friendly plastic production process according to claim 1, characterized in that: In step h), a layer of bio-based protective film is coated, wherein the concentration M of the protective film solution ranges from 3 to 8%, the film thickness N after coating ranges from 0.05 to 0.1 mm, and the formula M×N≤0.4 is satisfied; Prepare a bio-based protective film solution with a concentration M of 3 to 8%, and spray the solution evenly on the surface of the product treated in step g) by spraying; after spraying, control the drying temperature T19 to 50° C. to 70° C. to solidify the film layer; under the drying temperature condition, maintain the drying time T20 to 20 to 40 minutes; After the drying time was complete, the film thickness N was measured to be between 0.05 and 0.1 mm.

10. A process for producing biodegradable and environmentally friendly plastics according to claim 9, characterized in that: In step i), in the aging test, the light intensity I ranges from 500 to 1000 lux, the humidity H ranges from 60 to 80%, and satisfies the formula I×H≤80000; Placing a light source with a light intensity I of 500 to 1000 lux on the coated product in step h); under the light condition, controlling the ambient humidity H to be 60 to 80%; under the light and humidity conditions, the continuous exposure time T21 is 30 to 60 days; After the medium exposure time, evaluate the change in physical properties of the product ΔP, where ΔP is the difference in physical properties before and after exposure. After the evaluation, place the sample in a biodegradable environment, control the temperature T22 to 25°C to 35°C, and maintain the humidity H unchanged, and monitor its degradation rate R, where R represents the percentage of mass loss per unit time.

Citation Information

Patent Citations

  • Polylactic acid / starch full bio-based degradable composite material and preparing method thereof

    CN102604349A

  • Starch and polylactic acid composite material and preparation method thereof

    CN102863654A

  • Biodegradable thermoplastic polymer compostion, method for its manufacture and use thereof

    EP3064542A1

  • Bio based biodegradable polymer compositions and use of same

    US20070129467A1

Cited By

  • Modified thermoplastic material and preparation method thereof

    CN119875313A